Wimereux, station balnéaire de villégiature (1860-1930) : la « machine à habiter » - Olivier Lazzarotti (In Situ)
The design and construction of Wimereux, in the Pas-de-Calais department, began in the 1860s and came to an end in the 1930s. The study of this particular resort, at one and the same time totally unique and perfectly banal, allows for an analysis of the mechanisms of a tourist enterprise based on a model already tried out elsewhere, the seaside resort. Far from the delights of the seaside, the success of the resort is the result of a rigorous logic of economic and political development. By the affirmation of the place and by the enrichment of its promoters, and with the complicity of some holidaymakers, a particular society, the society of Wimereusiens, can be identified. This example illustrates the political and existential dimensions of the relations to a place and to the concept of « dwelling », recently developed in geography.